2023
DOI: 10.1177/10711007231171084
|View full text |Cite
|
Sign up to set email alerts
|

Total Ankle Arthroplasty: Does Obesity Matter?

Abstract: Background: There is limited data evaluating the effect of obesity on outcomes following total ankle arthroplasty (TAA), especially in adequate sample sizes to detect impacts on patient-reported outcomes (PROs). The purpose of this study was to assess the effect of obesity on complication rates and PROs. Methods: This was a single-institution, retrospective study of 1093 primary TAA performed between 2001 and 2020. Minimum follow-up was 2 years. Patients were stratified by body mass index (BMI) into control (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…They found that obese patients did not experience increased rates of complication, revision, or infection after TAR. 9 In addition, patients with obesity reported, on average, worse pre-and postoperative function, pain, and general health status; however, the magnitude of the change in PRO scores was similar across the BMI groups. More broadly, Jennison et al 8 analyzed various risk factors for failure of TAR in a retrospective UK registry-based study of 5562 patients.…”
mentioning
confidence: 89%
See 3 more Smart Citations
“…They found that obese patients did not experience increased rates of complication, revision, or infection after TAR. 9 In addition, patients with obesity reported, on average, worse pre-and postoperative function, pain, and general health status; however, the magnitude of the change in PRO scores was similar across the BMI groups. More broadly, Jennison et al 8 analyzed various risk factors for failure of TAR in a retrospective UK registry-based study of 5562 patients.…”
mentioning
confidence: 89%
“…In this issue of FAI , 2 articles provide important insights into the effect of body mass index (BMI) on TAR outcomes. 8,9 Kim et al 9 evaluated the effect of obesity on complication rates and patient-reported outcome (PRO) measure scores in a single-institution, retrospective comparative study of 1093 primary TARs. They found that obese patients did not experience increased rates of complication, revision, or infection after TAR.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…12,21,54 However, the role of excess weight or obesity as a prognostic factor for TAA is still under debate. 20,31,33,37…”
Section: Introductionmentioning
confidence: 99%